AN EXPLORATION OF POTENTIAL REWARDS IN ENGLISH FOR YOUNG LEARNER (EYL) CLASSROOM - Prawiro, Indra Yoga; Anggrarini, Natalia; Anggrarini, Natalia (Wiralodra English Journal, 2019)
In the 21st century, many parents try to introduce foreign language since earlier. The introduction is started since very beginning because some experts believed that the students who learn foreign language especially English on their primary schools or pre-schools, it will contribute the successful of them in learning language in the next level Ferrandino and Tirozzi as cited in MacDonell, C. (2007:1). This research is a case study. It aims to find out the use of potential rewards in kindergarten schools. This study will also investigate some challenges and efforts of five EYL teachers in teaching English. Hence this study will also focus on the benefits of potential rewards in motivating the EYL students in learning English. The result showed that social reinforcers is the most used reward and three activities that usually implemented in the class are giving applause, smiles and teacher?s signature. Then, there are two main challenges in teaching English in kindergarten school. The first is the use of technology and the second is classroom management. While the efforts used in teaching EYL are the use of media, strategy and rewards. So, the students will be more fun and enjoyable in learning English. Then, the last is the benefits. The result showed that by implementing the rewards system in the class. It can encourage the students to achieve the target learning. The students are happy to follow the instructions from the teacher and can complete the task well.